2015
DOI: 10.1093/intqhc/mzu098
|View full text |Cite
|
Sign up to set email alerts
|

What are incident reports telling us? A comparative study at two Australian hospitals of medication errors identified at audit, detected by staff and reported to an incident system

Abstract: ObjectivesTo (i) compare medication errors identified at audit and observation with medication incident reports; (ii) identify differences between two hospitals in incident report frequency and medication error rates; (iii) identify prescribing error detection rates by staff.DesignAudit of 3291patient records at two hospitals to identify prescribing errors and evidence of their detection by staff. Medication administration errors were identified from a direct observational study of 180 nurses administering 745… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 33 publications
6
105
2
2
Order By: Relevance
“…The occurrence of incidents with respect to organization and processes [16,17], surgery and anaesthesia [18][19][20], and medication [6,[20][21][22][23][24][25] were described, too.…”
Section: What Was Reported?mentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of incidents with respect to organization and processes [16,17], surgery and anaesthesia [18][19][20], and medication [6,[20][21][22][23][24][25] were described, too.…”
Section: What Was Reported?mentioning
confidence: 99%
“…One element is to ensure and promote effective work at all levels to increase patient safety. These can be mediated by education and training to increase the knowledge and skills of the staff [25,27,30]. Another aspect is the implementation of a "no blame" error and feedback culture and the security of an absolutely anonymous reporting system [4,37,41,44].…”
Section: Obstructive and Assisting Aspectsmentioning
confidence: 99%
“…Such barriers include, for example, fear of blame and repercussions, poor usability of incident reporting systems, perceptions among doctors that incident reporting is a nursing process, lack of feedback to staff who report incidents, and lack of visible improvements to the local work environment as a result of reported incidents (Benn et al, 2009, Braithwaite et al, 2010, Lawton and Parker, 2002, Macrae, 2015, Sujan, 2012, Sujan et al, 2011a. Among management staff in particular, there continues to be widespread misperception that incident reporting systems might be useful for monitoring incident frequencies, despite evidence that suggests that incident reporting data are poor indicators of actual incident frequencies (Westbrook et al, 2015). It has been suggested that the focus of learning from incidents in health care has been too much on collecting and categorising data (Macrae, 2015, Anderson andKodate, 2015), whereas successful learning from experience should inherently be a social and participative process (Macrae, 2015, Lukic et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Among management staff in particular, there continues to be widespread misperception that incident reporting systems might be useful for monitoring incident frequencies, despite evidence that suggests that incident reporting data are poor indicators of actual incident frequencies [74].…”
Section: The Challenges Of Organisational Learning In Healthcarementioning
confidence: 99%